2019
DOI: 10.1155/2019/7304786
|View full text |Cite
|
Sign up to set email alerts
|

Apheresis Therapy for Steroid-Resistant Idiopathic Nephrotic Syndrome: Report on a Case Series

Abstract: Idiopathic nephrotic syndrome (INS) represents 15%–30% of adulthood glomerulopathies. Corticosteroids have been the main treatment for decades and are effective in 70% of minimal-change disease patients and ~30% of focal segmental glomerulosclerosis patients. Multidrug-resistant (steroids, calcineurin-inhibitors, cyclophosphamide, mycophenolate-mofetil, rituximab) idiopathic nephrotic syndrome is a major therapeutic challenge in nephrology. Apheresis (double-filtration plasmapheresis or semi specific immunoads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…With the exception of studies on LDL-A, all the available data relating to the potential value of apheresis for treating refractory INS in adulthood originate exclusively from case reports. 13 , 26 , 27 , 28 Our study focusing exclusively on adult patients with refractory INS suggests that apheresis may be a relevant treatment option in some cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the exception of studies on LDL-A, all the available data relating to the potential value of apheresis for treating refractory INS in adulthood originate exclusively from case reports. 13 , 26 , 27 , 28 Our study focusing exclusively on adult patients with refractory INS suggests that apheresis may be a relevant treatment option in some cases.…”
Section: Discussionmentioning
confidence: 99%
“…Naciri Bennani et al. 26 recently described 3 cases that suggested that double-filtration plasmapheresis or semi-specific IA could successfully treat INS in patients in whom conventional therapies had failed. With the exception of studies on LDL-A, all the available data relating to the potential value of apheresis for treating refractory INS in adulthood originate exclusively from case reports.…”
Section: Discussionmentioning
confidence: 99%